Intra-plant variation in seed weight and seed protein content of cowpea - Iseki, K.; Olaleye, O.; Ishikawa, H. (Informa UK Limited, 2020)
Seed size and protein content are the major breeding objectives for cowpeas (Vigna unguiculata). However, intra-plant variation in these traits causes heterogeneous seed quality and seed depreciation. To determine the causes and severity of intra-plant variation in cowpea single seed weight and protein content, seeds from individual plants were analyzed in relation to their positional effects. Associations between positional variables and seed traits were revealed by additive Bayesian network analysis, and the graphical models were compared for different accessions. Intra-plant variation in single seed weight and protein content were large compared to the variations in genetic resources, and these variations are thought to be related to the source/sink ratio within a plant. In accessions with longer flowering periods, the later-flowering peduncles on the upper nodes produced comparatively larger seeds due to a greater availability of assimilated carbon from leaves that maintain their greenness. While, in accessions with shorter flowering periods, the earlier-flowering peduncles on the lower nodes produced relatively larger seeds because less carbon is available at the later filling periods due to rapid senescence. For all accessions, protein content was higher in seeds derived from later-flowering peduncles and in pods with lower seed numbers. The nitrogen source/sink ratio may be higher in the later filling period because of a smaller number of filling seeds and a higher availability of nitrogen remobilized from senescing leaves and stems.